THE MODULE «VIRTUAL ELECTRONIC BOARD» OF DISTANCE LEARNING SYSTEM «KHERSON VIRTUAL UNIVERSITY 2.0» - E. O. Kozlovskij; V. V. Ljakutin; H. M. Kravtsov (Kherson State University, 2010)
Results of structure modeling, construction of learning model and development of program module Whiteboard - a virtual electronic board of distance learning system «Kherson Virtual University» are presented.